Hubungan Kepatuhan Diet Rendah Garam Dengan Tekanan Darah Pada Pasien Hipertensi Di Puskesmas Pasar Ikan Kota Bengkulu - Novitasari, Mistati; Sutrisna, Marlin; Sari, Lia Novita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Hypertension is one of the most common chronic diseases in the community and serves as a major risk factor for heart disease and stroke. One effective non-pharmacological approach to controlling blood pressure is the adoption of a low-salt diet. However, patient adherence to dietary recommendations often remains low. This study aimed to examine the relationship between compliance with a low-salt diet and blood pressure among hypertensive patients. A quantitative research design with a cross-sectional approach was employed. The sample consisted of hypertensive patients selected using purposive sampling. Data were collected through the Dietary Approaches to Stop Hypertension (DASH) questionnaire and blood pressure measurements, and analyzed using the Chi-square test. The results showed that the majority (76.8%) of respondents were compliant with a low-salt diet, and most were categorized as having grade 1 hypertension (62.2%). Statistical analysis revealed a significant relationship between compliance with a low-salt diet and blood pressure levels (p < 0.05). In conclusion, higher compliance with a low-salt diet is associated with a greater likelihood of achieving normal or controlled blood pressure. It is recommended that healthcare providers enhance education and monitoring efforts regarding dietary adherence as part of comprehensive hypertension management.